2023
DOI: 10.3389/fnhum.2023.1131986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive practice of motor tasks on somatosensory gating

Abstract: IntroductionDuring voluntary muscle contraction, the amplitude of the somatosensory evoked potential (SEP) is reduced by inhibiting sensory information from a peripheral nerve supplying the contracted muscle. This phenomenon is called “gating.” We reported that participants with good motor skills indicated strong suppression of somatosensory information. The present study investigated the effects of motor performance improvement following repetitive practice on the SEP amplitude.MethodsThe ball rotation task (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…During these trials, the participants were standing on the surface (i.e., biomimetic or smooth, see below for their description) on which they were standing at the start of their experimental session (see below). Note that this training session, which lasted ~3 min, unlikely altered the sensory gating [see ( 35 ), for evidence of unaltered SEP gating during repetitive practice]. The analyses showed that, for both types of surfaces, the amplitude of the shear forces exerted by participants on the platform in the active task was fairly similar to those recorded in the passive task (see Figure 2A ).…”
Section: Methodsmentioning
confidence: 88%
“…During these trials, the participants were standing on the surface (i.e., biomimetic or smooth, see below for their description) on which they were standing at the start of their experimental session (see below). Note that this training session, which lasted ~3 min, unlikely altered the sensory gating [see ( 35 ), for evidence of unaltered SEP gating during repetitive practice]. The analyses showed that, for both types of surfaces, the amplitude of the shear forces exerted by participants on the platform in the active task was fairly similar to those recorded in the passive task (see Figure 2A ).…”
Section: Methodsmentioning
confidence: 88%